2014
DOI: 10.1002/lt.23951
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain after orthotopic liver transplantation: Is nonalcoholic fatty liver disease cirrhosis a risk factor for greater weight gain?

Abstract: Posttransplant weight gain is common after orthotopic liver transplantation. We sought to determine the extent of weight gain at 5 years after transplantation in patients with nonalcoholic fatty liver disease (NAFLD) cirrhosis versus patients with other types of cirrhosis (non-NAFLD). We studied 126 liver transplants performed between 2005 and 2007 at Saint Luc Hospital, University of Montreal. Seventeen of the 126 patients (13.5%) had NAFLD cirrhosis. Ascites volume was difficult to assess, so we used the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…As we reported, transplant patients often develop IR and an increase in body weight [ 1 ]. Interestingly, Kouz et al [ 55 ] demonstrated that in patients transplanted for NASH-cirrhosis, most of the weight gain occurs in the first year after LT, while the increase of the weight is more progressive in subjects with a different etiology. However, regardless of the kind of pre-LT liver disease, after LT a relevant increase in dietary intake can be found, especially in patients with pre-LT severe dietary restrictions, gastrointestinal symptoms or anorexia.…”
Section: Therapeutic Approach Against Post-transplant Dysmetabolismentioning
confidence: 99%
“…As we reported, transplant patients often develop IR and an increase in body weight [ 1 ]. Interestingly, Kouz et al [ 55 ] demonstrated that in patients transplanted for NASH-cirrhosis, most of the weight gain occurs in the first year after LT, while the increase of the weight is more progressive in subjects with a different etiology. However, regardless of the kind of pre-LT liver disease, after LT a relevant increase in dietary intake can be found, especially in patients with pre-LT severe dietary restrictions, gastrointestinal symptoms or anorexia.…”
Section: Therapeutic Approach Against Post-transplant Dysmetabolismentioning
confidence: 99%
“…Rapid weight gain after liver transplant is a worldwide phenomenon with 16-46% of liver transplant recipients (LTRs) becoming obese in the first year after transplant. [1][2][3][4][5][6][7][8] There is a higher prevalence of metabolic syndrome in LTRs compared with the general adult population and this appears to predispose to increasing cardiovascular disease risk, graft rejection, infection and other complications. 9 Adjusting to a liver transplant is a complex process which incorporates both physical and mental components of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to address this aspect in a group of patients well known to acquire weight after the operation . Approximately one‐third to two‐thirds of the patients are obese soon after LTx. Of the 270 patients evaluated in the present study, 64.1% were classified as having excessive weight and 23.3% were classified as obese.…”
Section: Discussionmentioning
confidence: 94%